2017
DOI: 10.1038/srep44944
|View full text |Cite
|
Sign up to set email alerts
|

Grid-enhanced X-ray coded aperture microscopy with polycapillary optics

Abstract: Polycapillary devices focus X-rays by means of multiple reflections of X-rays in arrays of bent glass capillaries. The size of the focal spot (typically 10–100 μm) limits the resolution of scanning, absorption and phase-contrast X-ray imaging using these devices. At the expense of a moderate resolution, polycapillary elements provide high intensity and are frequently used for X-ray micro-imaging with both synchrotrons and X-ray tubes. Recent studies have shown that the internal microstructure of such an optics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In the adult disc, Col1 is predominantly confined to the outer annulus fibrosus 1 except during aging and degeneration when the NP becomes more fibrous 63 . Consistent with our results, however, Col1 mRNA and protein have been demonstrated previously in the developing notochord and NP in humans and mice 12 , 54 , 57 , 65 . We also found significantly elevated Col6 mRNA expression at P0 (Table 4 , Fig.…”
Section: Discussionsupporting
confidence: 94%
“…In the adult disc, Col1 is predominantly confined to the outer annulus fibrosus 1 except during aging and degeneration when the NP becomes more fibrous 63 . Consistent with our results, however, Col1 mRNA and protein have been demonstrated previously in the developing notochord and NP in humans and mice 12 , 54 , 57 , 65 . We also found significantly elevated Col6 mRNA expression at P0 (Table 4 , Fig.…”
Section: Discussionsupporting
confidence: 94%
“…For X-ray detection, we used two X-ray cameras. The first was an 80 mm × 80 mm Gadox scintillator, which was lens-coupled to a 4M pixel sCMOS camera (Photonic Science) [5]. The spatial resolution was limited to approximately 150 µm in the image centre.…”
Section: Methodsmentioning
confidence: 99%
“…However, depth resolution was achieved by scanning the sample in both the lateral and axial directions and the main objective of single exposure 3D imaging has not been realized. Moreover, coded aperture approach has strong disadvantages, and the weak signalto-noise ratio made the imaging of weak features via phasecontrast impractical 28 . More recently, it was demonstrated that individual capillaries 29 (or even defects 30 ) inside a polycapillary optics can be used to generate an array of secondary quasi-point x-ray sources and to obtain replicated projections of planar objects that are placed at the focal plane in the socalled multipoint projection geometry.…”
mentioning
confidence: 99%